Analisis Faktor Yang Mempengaruhi Persalinan Induksi Di Rumah Sakit Citra Sari Husada Karawang - Jusmawati; Nur’aeni , Teti (Jurnal Keperawatan Muhammadiyah, 2024)
Objective : Induction of labor is an attempt to get labor to start before or after a full-term pregnancy by stimulating (stimulation) the onset of pregnancy. .To find out the results of the analysis of the factors that influence labor induction at Citra Sari Husada Hospital, Kelari District, Karawang Regency. Methods : This research uses a correlational descriptive quantitative method with purposive sampling with a sample of 23 people. Data techniques include uivariate analysis using frequency distributions and bivariate analysis using statistical calculations using the SPSS program. Result: The results of the analysis show a significant relationship between postterm pregnancy and labor induction, with a consistent significance value below 0.05, although it is necessary to consider these limitations and notes, the results of this study generally support the influence of post-term pregnancy on the tendency for labor induction, namely, 78.5% underwent labor induction. Conclusions and Suggestions: This research shows that factors such as Premature Rupture of Membranes (PROM), Late Pregnancy, and Hypertension have a significant influence on the decision to induce labor at Citra Sari Husada Hospital.